Minimization of polymerization shrinkage effects on composite resins by the control of irradiance during the photoactivation process - Guimaraes, Gabriel Felipe [UNESP]; Marcelino, Edilmar [UNESP]; Cesarino, Ivana [UNESP]; Vicente, Fabio Bossoi [UNESP]; Grandini, Carlos Roberto [UNESP]; Simoes, Rafael Plana [UNESP] (Univ Sao Paulo Fac Odontologia Bauru, 2018)
High levels of shrinkage stress caused by volumetric variations during the activation process are one of the main problems in the practical application of composite resins. Objective: The aim of this study is to reduce the shrinkage stress and minimize the effects caused by composite resin volumetric variation due to the photopolymerization. In this way, this work proposes a systematic study to determine the optimal dimming function to be applied to light curing processes. Material and Methods: The study was performed by applying mathematical techniques to the optimization of nonlinear objective functions. The effectiveness of the dimming function was evaluated by monitoring the polymerization shrinkage stress during the curing process of five brands/models of composites. This monitoring was performed on a universal testing machine using two steel bases coupled in the arms of the machine where the resin was inserted and polymerized. The quality of the composites cured by the proposed method was analyzed and compared with the conventional photoactivation method by experiments to determine their degree of conversion (DC). Absorbance measurements were performed using Fourier-transform infrared spectroscopy (FT-IR). A T-test was performed on DC results to compare the photoactivation techniques. We also used scanning electron microscopy (SEM) to analyze in-vitro the adhesion interface of the resin in human teeth. Results: Our results showed that the use of the optimal dimming function, named as exponential, resulted in the significant reduction of the shrinkage stress (similar to 36.88% +/- 6.56 when compared with the conventional method) without affecting the DC (t=0.86, p-value=0.44). The SEM analyses show that the proposed process can minimize or even eliminate adhesion failures between the tooth and the resin in dental restorations. Conclusion: The results from this study can promote the improvement of the composite resin light curing process by the minimization of polymerization shrinkage effects, given an operational standardization of the photoactivation process.
Keywords: Dental restoration; Composite resins; Light-curing of dental adhesives